CONTEXTUALIZING ALISHER NAVOI AND THE TIMURID RENAISSANCE - F. f.n. Turdiyeva N.Y Qahharova Mehriniso Qahramonovna Samarqand davlat chet tillari instituti magistranti (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
Alisher Navoi, Timurid Renaissance, Chagatai Turkic language, Islamic literature, Central Asia, poetry, mysticism, Annotation: This article explores the life and legacy of Alisher Navoi (1441-1501), a pivotal figure in Timurid Renaissance literature. It delves into the historical context of the Renaissance, highlighting the Timurid commitment to scholarship, patronage of the arts, and the rise of Chagatai Turkic as a major literary language. The article focuses on Navoi’s contributions, including his mastery of Chagatai, his epic poems like the "Khamsa," and his exploration of themes like love, mysticism, and ethics. It discusses his influence on writers across Central Asia, the Ottoman Empire, and Mughal India. Finally, the article emphasizes the lasting impact of Navoi and the Timurid Renaissance on Islamic culture and literature.